Czasopismo pedagogiczne „Chowanna” jako przejaw działalności Instytutu Pedagogicznego w Katowicach (PDF 6,03 MB) (Książnica Śląska, 2025)
The article describes the establishment and operation of one of themost important Polish scientific institutions founded in Upper Silesia in the interwar period – the Pedagogical Institute in Katowice.The paper presents the most critical goals, tasks and organizationof the Institute, which solemnly inaugurated its activity on October28, 1928. The most important periodical of the Institute – the pedagogical magazine “Chowanna” has been described in detail. “Cho-wanna” was published from 1929 to 1939. It was a scientific journalfor the first two years, theoretically developing pedagogical, psychological, sociological and cultural issues. Later on, it functionedas a supporter and advocate of Polish educational culture and broughtreaders closer to the activity of the Pedagogical Institute in Katowice.Since 1935, the regional supplement “Sprawy Szkolne na Śląsku”(School Affairs in Silesia) was attached to the magazine.